2019
DOI: 10.1021/acs.jafc.9b00569
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Enzymatic Hydrolysis with Alcalase and Papain Effectively Reduce Allergic Reactions to Gliadins in Normal Mice

Abstract: Gliadins are major allergens responsible for wheat allergies. Food processing is an effective strategy to reduce the allergenicity of gluten. In the present study, we determined the secondary and tertiary structures of gluten and gliadins treated by chemical, physical, and enzymatic means through FTIR, surface hydrophobicity, intrinsic fluorescence spectra, and UV absorption spectra. The results showed that the three treatments of phosphorylation and alcalase and papain hydrolyses significantly changed the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
5
34
0
Order By: Relevance
“…They reported that sequential use of alcalase and papain significantly reduced the gliadin content of hydrolyzed wheat flour, and the IgE reactivity of its gliadin. Similar results of reduced allergenicity of gliadins from alcalase-and papain-treated flours were reported in a Balb/c mouse model study (Xue et al, 2019). Therefore, two different lines of evidence (human IgE reactivity and mouse model IgE responses) suggest that potentially hypoallergenic gliadins can be produced using alcalase and papain hydrolysis.…”
Section: Enzyme Hydrolysis Of Wheat Can Reduce or Even Abolish Its Allergenicitysupporting
confidence: 80%
“…They reported that sequential use of alcalase and papain significantly reduced the gliadin content of hydrolyzed wheat flour, and the IgE reactivity of its gliadin. Similar results of reduced allergenicity of gliadins from alcalase-and papain-treated flours were reported in a Balb/c mouse model study (Xue et al, 2019). Therefore, two different lines of evidence (human IgE reactivity and mouse model IgE responses) suggest that potentially hypoallergenic gliadins can be produced using alcalase and papain hydrolysis.…”
Section: Enzyme Hydrolysis Of Wheat Can Reduce or Even Abolish Its Allergenicitysupporting
confidence: 80%
“…29 In the current study, gliadin-sensitized mice exhibited a typical Th2 response with high levels of IgE, histamine, and intestinal alterations, which were the same as the existing research results. 19,29 L-Arabinose had a certain relieving effect on adverse symptoms caused by an allergy with the regulation of IgE production and histamine release, and maintenance of intestinal barrier integrity, which corroborated the antiallergic effect of L-arabinose.…”
Section: ■ Discussionmentioning
confidence: 59%
“…ELISA analysis of IgE specific to gliadin in the serum was conducted as previously described. 19 The concentrations of IL-4, IFN-γ, and TGF-β in the serum were measured using Mouse IL-4, IFN-γ, and TGF-β ELISA kits.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Xue et al reported that gluten hydrolysis using papain leads to the modification of the conformational structures of gliadins, especially the secondary structure. [140] The enzymatic tests were carried out at 60 °C, pH 4.6, substrate concentration of 80 g gluten L À 1 , and a papain/gluten ratio of 200 U g À 1 . The authors observed a reduction of β-sheet (22 %), a slight increase in βturn (3 %) α-helix (2) for a hydrolysis degree of 20 %.…”
Section: Hydrolysis Of Gluten and Obtention Of Bioactive Peptidesmentioning
confidence: 99%